2009
DOI: 10.1136/jcp.2008.063461
|View full text |Cite
|
Sign up to set email alerts
|

LocalBorrelia burgdorferisensu stricto andBorrelia afzeliistrains in a single mixed antigen improves western blot sensitivity: Table 1

Abstract: The mixed antigen and revised interpretation criteria have been successfully incorporated into the routine diagnostic testing service, increasing the sensitivity of the in-house IgG western blot test for Scottish patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…The increased seroreactivity of the in-house western blot used in Scotland has been reported previously,6 and this study has identified, in addition to the specific bands, antibodies to 27 bands in serum of patients with suspected Lyme borreliosis that are not currently considered to be specific. Although six bands are significantly found more frequently in the sera of the western blot positive patients, three of these bands identified were outside the 99% confidence interval of the expected frequency and so are of particular interest.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The increased seroreactivity of the in-house western blot used in Scotland has been reported previously,6 and this study has identified, in addition to the specific bands, antibodies to 27 bands in serum of patients with suspected Lyme borreliosis that are not currently considered to be specific. Although six bands are significantly found more frequently in the sera of the western blot positive patients, three of these bands identified were outside the 99% confidence interval of the expected frequency and so are of particular interest.…”
Section: Discussionsupporting
confidence: 65%
“…All samples were screened by a commercial enzyme immunoassay (EIA) method (Zeus Scientific, Raritan, New Jersey, USA) and the equivocal and positive samples were tested by the confirmatory in-house IgG western blot which uses a local B burgdorferi sensu stricto and B afzelii antigen (50:50) mix 6. EIA negative samples from patients in whom there was a high clinical suspicion of Lyme borreliosis—for example, tick bite and rash or erythema migrans—were also tested by the confirmatory western blot assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 However, the antigen used and interpretation criteria were revised in April 2004, 9 June 2007 10 and October 2008. 5 In this study, all patients with a weak positive or positive Western blot result were classed as seropositive.…”
Section: Laboratory Testsmentioning
confidence: 99%
“…1 Rises in LB have been linked with improved diagnostics, raised awareness, changes in land use, increased tick density and burden of tick disease. 5 In Scotland the incidence of LB is highest in the Highlands, an area of high endemicity. 6 Scottish studies have therefore focused on this region and there is little information on the incidence and epidemiology of LB in other regions.…”
Section: Introductionmentioning
confidence: 99%